(untitled) (African Journal of Biomedical Research, 2024)
Vitamin D deficiency (VDD) has been associated with increased mortality in patients with COVID-19. The anti-inflammatory properties of vitamin D are vital when considering the heightened inflammation in COVID-19 patients. Although avalanche of reports are available on the plasma levels of vitamin D and C-reactive protein (CRP) in COVID-19 patients, information on the dynamics of CRP level changes in different categories of vitamin D status is lacking. Therefore, the plasma levels of CRP were determined in COVID-19 patients in different classifications of vitamin D status. Forty nine adults comprising 31 COVID-19 patients and 18 apparently healthy participants who served as controls were enrolled into this study. The plasma levels of high sensitivity-CRP (hsCRP) and vitamin D were determined using ELISA. Vitamin D status was classified as insufficient, sufficient, and intoxication as appropriate. None of the COVID-19 patients had vitamin D insufficiency while majority of the controls were vitamin D sufficient. The proportion of COVID-19 patients with vitamin D intoxication was significantly higher than in the controls. The median plasma levels of vitamin D and hsCRP were not significantly different between the COVID-19 patients and the controls. The median plasma level of hsCRP was slightly lower in the vitamin D intoxication group compared with the vitamin D sufficient group. Vitamin D intoxication is common among Nigerian patients with COVID-19 and the vitamin D intoxication is associated with low plasma hsCRP level. There is the need for public enlightenment on the dangers inherent in vitamin D supplement abuse in Nigerians.